Implementasi Pemenuhan Hak dan Kewajiban Warga Negara Indonesia di Bidang Pendidikan - Andi Bagasmulya; Afrizal Donny Prasetyo (Administratie: Jurnal Administrasi Publik, 2026)
Education is a fundamental right of every citizen, which to this day still faces various inequalities in its implementation, thus requiring in-depth study through scientific approaches to achieve comprehensive understanding. This research aims to identify the extent to which the right to education has been realized, understand the fulfillment of citizens’ obligations in supporting education, and formulate strategies and efforts to effectively optimize equitable education in Indonesia. The method used is a literature review by examining national articles published between 2020 and 2025 that are relevant to issues of citizens’ rights and obligations in the context of education. The results of the study indicate that the fulfillment of educational rights still faces significant obstacles, primarily due to disparities in educational infrastructure, uneven quality of teaching staff, and limited digital readiness. In addition, the implementation of citizens’ obligations in the field of education is also not yet optimal, influenced by low levels of educational literacy and various socio-economic barriers that hinder active community participation in supporting national education. The impact of this situation is an imbalance in access to and quality of education, which has the potential to widen social gaps and hinder the overall development of human resources in Indonesia.